Improved compressive strength and fracture toughness analysis of natural soil based geopolymer. (December 2021) - Nadeem, Muhammad; Ahmed, Furqan; Haq, Ehsan ul; Zain-ul-Abdein, Muhammad; Raza, Ali; Afzal, Umair; Bibi, Saima; Deen, Zeehsan Siraj
Abstract: Geopolymeric materials are playing vital role in the construction world due to their better properties and numerous applications. In this study, fracture toughness of natural soil based geopolymeric material has been investigated by three-point bending test of notched beam type specimens and improved compressive strength was achieved. Natural soil has been used as a main precursor while sodium silicate was used as alkaline activating solution. Better results of fracture toughness were achieved in the resulting geopolymeric materials that were investigated using three point bending test, load deflection behavior, Fourier transformed infrared spectroscopy (FTIR), degree of geopolymerization and scanning electron microscopy (SEM). Maximum fracture toughness (1.432 MPa m 1/2 ) and compressive strength (25.5 MPa) with minimum porosity (9.724%) was achieved by using 75% natural soil and 25% sodium silicate solution which is the highest compressive strength compared to previous researches on natural based geopolymeric materials. Highlights: Natural Soil can be used as abundantly available precursor for synthesis of geopolymers. Better Fracture toughness was achieved by changing composition. Natural soil based geopolymer are green to the environment. Resultant geopolymers have substantial application in construction world.